Handbook of administrative ethics - Cooper, Terry L., 1938- (Marcel Dekker, 2001)
This handbook follows the discussion of ethics in significant pieces of public administration literature from the late-19th century to the start of the 21st. It offers theoretical perspective, illustrative cases, and empirical research. This edition includes a new chapter on military ethics.
Keywords: Civil service ethics -- United States.; Government executives -- Professional ethics -- United States.; Civil service ethics.; Government executives -- Professional ethics.; Fonctionnaires -- Déontologie -- États-Unis.; Hauts fonctionnaires -- Déontologie -- États-Unis.; Fonctionnaires -- Déontologie.; Hauts fonctionnaires -- Déontologie.; POLITICAL SCIENCE -- General.; Civil service ethics; Government executives -- Professional ethics; United States; Humaniora -- Filosofi.